Effects of Intratympanic Steroid on Cisplatin Ototoxicity: An Electrophysiological and Ultrastructural Study - (:unkn) unknown (AKAD DOKTORLAR YAYINEVI, 2018)
Ototoxicity refers to the inner ear dysfunction caused by a drug or a chemical agent which manifests as hearing loss or balance impairment, or both. Currently, antibiotics, diuretics, anti-inflammatory drugs, antineoplastic agents, antimalarial drugs and some other agents are known to cause ototoxicity. Cisplatin is an antineoplastic agent for which the ototoxicity incidence may vary based on the treatment protocol. In the present study, we aimed to perform an electrophysiological and ultrastructural evaluation regarding the protective effectiveness of intratympanic steroids on cisplatin ototoxicity. Electrophysiological assessment included tympanometry and auditory brainstem response (ABR), and 16 guinea pigs (32 ears) with normal hearing were randomly assigned to 4 groups as follows: control, cisplatin, cisplatin/steroid and cisplatin/physiological saline. Following the electrophysiological measurements, temporal bones were dissected for ultrastructural examinations. In the cisplatin group, a statistically significant (p<0.05) threshold difference was noted for the ABR test versus the other groups while this threshold difference was lower in the cisplatin/steroid group compared to the other groups. Ultrastructural evaluations revealed abnormal outer hair cell stereocilia morphology and severe degenerative changes in the cisplatin and cisplatin/physiological saline groups. Mild degenerative alterations were seen in the outer hair cell stereocilia morphology in the guinea pig cochlea administered with intratympanic steroid. We believe intratympanic steroid administration showed protective effectiveness on the cisplatin-induced ototoxic damage in our study.
Keywords: Cisplatin; Electron microscopy; Auditory evoked brainstem responses; Methylprednisolone; GUINEA-PIG; DEXAMETHASONE; METHYLPREDNISOLONE; PREVENTION; PERILYMPH; INJECTION; TOXICITY; PROTECTS; HEARING; CANCER